Implementation of Community-Based Learning (CBL) in cultivating students’ interests and talents: a case study of Sekolah Alam Bogor - Irwansyah Irwansyah; Luthfi Wibawa; Yudan Hermawan (Educenter : Jurnal Ilmiah Pendidikan, 2026)
The SMX School of Maker program under Sekolah Alam Bogor implements a Community-Based Learning (CBL) approach that emphasizes experiential learning and active engagement with the community. However, collaboration between the school and community partners in designing CBL programs has not yet been fully optimized. This study aims to examine the implementation of CBL at SMX, identify supporting and inhibiting factors, and evaluate its impact on students’ interests and talents. Using a qualitative case study method, data were collected through in-depth interviews, observations, and documentation. Informants included the Foundation Chair, the Director of Sekolah Alam, the Chair of the Nusantara Sekolah Alam Network, teachers or facilitators, students, and community representatives. Data were analyzed using descriptive qualitative techniques. The findings reveal that CBL implementation involves several stages: collaborative curriculum development with community partners; preparation of 80% of the syllabus through inter-community contributions; structured academic planning through salamik and early-year coordination; direct integration of facilitators and community members in learning activities; and experience- and project-based learning as the instructional core. Supporting factors include SAB’s vision, mission, pillars, and active stakeholder involvement. Nevertheless, rigid adherence to these foundational principles may also pose challenges. Integrating Project-Based Learning (PjBL) further strengthens CBL in enhancing students’ interests and talents.